Effective Communication Techniques in Conveying Religious Values Through Animated Films (Study at Al Marjan Elementary School, Bengkulu City) - Anisa Dwi Saputri; Anis Endang; Bayu Risdiyanto (Penerbit Jurnal Indonesia, 2023)
This research purpose is to describe dffective communication in delivering religious values with Animated movie. This research is gwantitative research and data are collected by using observation. interview and documentation. The result of this research shows hat efective communication technigues which used by teachers at SD AL MARJAN Bengkulu city in delivering religious values by building eredibiliay On students by creating learning system becomes fa, such as Watch Upin and Ipin movie together. Teachers tricd to obtain students